The effect of synthetic silica on ultrafiltration PSf membrane - Harun, Zawati (Universiti Teknologi Malaysia, 2013)
This study investigates the effects of synthetic silica(SiO2)with different weight percentage concentrations on the morphology and performance of the polysulfone (PSf) and polyethelene glycol (PEG) based membrane ultrafiltration (UF). Phase inversion method was used to prepare PSf/PEG ultrafiltration (UF) flatsheet membrane. SiO2 and N-Methyl 2 Pyrrolidone (NMP) were used as an additive and solvent respectively. The fabricated membrane was characterized by scanning electron microscope (SEM), X-ray diffraction (XRD) and the performances of the membranes were measured in term of pure water flux by using distilled water and solute rejection at different wastewater concentration at 50%, 75% and 87.5%. The result showed that the addition of 2% silica in the dope solution increased the permeation in terms pure water flux and the best rejection with 62 Lm-2 h-1 and 89% (at 87.5 % waste water dilution) respectively